Mexico : Earnings Inequality after Mexico's Economic and Educational Reforms, Volume 1. Main Document - World Bank (Washington, DC, 2013)
The study reviews the forces driving Mexico's inequality, in particular, the recent expansion in earnings inequality, emphasizing the roles of education on: establishing an analytical framework, that allows interaction between education, and labor market; examining the evolution of earnings inequality, following the macroeconomic, and educational policies of the 80s, and 90s; exploring best practices for the use, and allocation of public educational resources, in light of foreseeable increases in earnings inequality; and, identifying those areas of educational public policy, which impact student graduation. The study argues on the student's decision-making at the secondary, and tertiary levels, concerning the disciplines to pursue, - a choice clearly influenced by several factors - such as taste, abilities, family background, etc. Though some factors may be intrinsic, others could be used as policy tools, to provide advice on best study options, but insufficient effort on the part of educational institutions, and weak information, restrain best option selection. Theoretical support is suggested, to develop basic education, and increase access to the poor; upgrade the level of secondary education; and, improve financial access to higher education. The study contains two volumes, Volume 1 - the main document, summarizes the findings of the background papers, contained in volume 2.